Symposium 2: Change for networked learning - Beaty, Liz; Cousin, Glynis; Deepwell, Frances; Banks, Sheena; Powell, Adrian (Proceedings of the International Conference on Networked Learning, 2002)
This symposium aims to bring together research on the management of change issues in the introduction of elearning in higher education.. Networked learning has thrown many challenges to the current structure and organisation of higher education. Universities have been variously attempting to make use of opportunities of the new technology and at the same time to respond to the inevitable consequence of rapid system changes. The volatile nature of change in higher education has prompted many experiments and the papers in the symposium will report on research from major change initiatives within institutions and across institutions. The research papers report on the effects of strategic management and policy direction. The research has mainly been conducted as action research and case study research. The findings are based on longitudinal analyses of implementation of strategies over a period of three to four years. Two of the three papers (Coventry University and University of Sheffield) are based on individual institutions in England where different approaches have been taken to the introduction of elearning and the third is based on an analysis of trans-institutional change fostered in Scotland through the Virtual Learning Space (VLS) initiative. The Symposium will contribute to the conference themes of elearning, and the e-University, and to methodologies for researching networked learning. In relation to the first theme this symposium will focus on institutional level issues of management and policy and consider the aims and appropriate structure for universities in a networked world. The research reported will also offer a contribution to issues of researching the management of change in networked learning. The case studies reported are of a wider scope than many existing case studies and have data related to an era of unprecedented change which may in time be viewed as transformational. Papers: Introducing E-learning via a Community Network: a Teaching and Learning Strategy in Action Liz Beaty, Glynis Cousin and Frances Deepwell Developing Institutional Readiness for Implementing Networked Learning Sheena Banks and Adrian Powell Peer-to-peer Networked Learning across Institutions: The Virtual Learning Space and the Support of Staff Development Rachel Harris and Rory Ewins